Inclusive and sustainable economic transformation: Ways forward in low- and middle-income countries - Vidya Diwakar; Tony Mwenda Kamninga; Tim Kelsall; Sam Pickard; Sherillyn Raga; Andrew W. Shepherd; Foqoruddin Al Kabir; Hamidah Busyrah; Balgis Inayah; Fahmida Khatun; Mizan R. Khan; Elvin Nyukuri (ODI Global, 2025)
Can developing economies achieve growth that benefits everyone and protects the planet? This report explores how low- and middle-income countries (LMICs) can achieve inclusive and sustainable economic transformation (ISET) - where economic growth benefits all of society and protects our planet. Traditional economic models often prioritise profit over people and the environment. This report challenges that approach, offering a new vision for development where prosperity is shared by all and safeguards the planet for future generations. The report features case studies from Bangladesh, Indonesia and Kenya, showcasing how these countries are striving to implement policies that promote economic growth, social inclusion and environmental sustainability, as well as analysis of manufacturing, agriculture, energy and informal economies and the role of climate finance in promoting ISET.
Keywords: 330; Climate finance; Development finance; Economic transformation; Economic growth; Environment; Green growth; Asia; Bangladesh; Indonesia; Kenya; Africa